2017
DOI: 10.21061/jte.v29i1.a.5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Instructor Teaching Style and Content Course on Mathematics Anxiety of Preservice Teachers

Abstract: Integrative-STEM methodologies entail integrating multiple disciplines with active design-centric teaching and learning methods. If math anxiety is prevalent, for teachers or students, then both the level of integration and design thinking may be limited. This quantitative study of 160 preservice teachers investigated how math anxiety was impacted by (a) a required math content course, (b) instructor teaching style, and (c) academic and disciplinary major. Significance analyses included t-tests, nonparametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Perhaps the reason is related to the instructors’ teaching styles. Some studies indicated that students’ learning outcomes [ 54 ] and learning anxiety [ 55 ] were related the instructors’ teaching styles. To avoid the error of experiment caused by instructors, the same instructor was used in these four activities.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the reason is related to the instructors’ teaching styles. Some studies indicated that students’ learning outcomes [ 54 ] and learning anxiety [ 55 ] were related the instructors’ teaching styles. To avoid the error of experiment caused by instructors, the same instructor was used in these four activities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been observed that teachers with a negative predisposition toward teaching science and mathematics are perceived by students as hostile and indifferent and students remember having been humiliated by them in front of their classmates. Particularly, girls remember having been ridiculed with greater frequency than boys; girls also remember having received less formative feedback from teachers (Van der Sandt & O'Brien, 2017).…”
Section: / 15mentioning
confidence: 99%
“…Looney et al (2017) posited that helping teachers become more proficient at teaching math could create positive emotions towards math and lead to an improvement in their teaching of math. Van der Sandt and O'Brien (2017) found that one effective strategy for reducing teacher anxiety is to offer a math content course where teachers develop a conceptual understanding of math, explore problems, and communicate their understanding in various ways. This helped to build teachers' content knowledge of mathematics and provided them with opportunities to explore a variety of math manipulatives and strategies for solving problems.…”
Section: Professional Learningmentioning
confidence: 99%